Daily life in ancient China - Pu, Muzhou 1952- (Cambridge University Press, 2018)
In this volume, Mu-chou Poo offers a new overview of daily life in ancient China. Synthesizing a range of textual and archaeological materials, he brings a thematic approach to the topic that enables a multi-faceted understanding of the ideological, economical, legal, social, and emotional aspects of life in ancient China. The volume focuses on the Han period and examines key topics such as government organization and elite ideology, urban and country life, practical technology, leisure and festivity, and death and burial customs. Written in clear and engaging prose, this volume serves as a useful introduction to the culture and society of ancient China. It also enables students to better understand the construction of history and to reflect critically on the nature of historical writing
Keywords: Geschichte 206 v. Chr.-220; Handynastie; Alltag; China / Social life and customs / To 221 B.C.; China / Social life and customs / 221 B.C.-960 A.D.; China